Safety of edoxaban, an oral factor Xa inhibitor, in Asian patients with non-valvular atrial fibrillation - Chung, Namsik; Jeon, Hui-Kyung; Lien, Li-Ming; Lai, Wen-Ter; Tse, Hung-Fat; Chung, Wook-Sung; Lee, Tsong-Hai; Chen, Shih-Ann (Thrombosis and Haemostasis, 2011)
Edoxaban is an oral, reversible, direct factor Xa inhibitor in phase III clinical development for the prevention of stroke in atrial fibrillation (AF). A phase II study was undertaken to evaluate the safety and efficacy of edoxaban in Asian patients with non-valvular AF with CHADS2 score ≥1. In a multicentre, active-controlled, double-blind edoxaban and open-label warfarin, parallel-group study, a total of 235 patients from four Asian countries were randomly assigned to edoxaban 30 mg qd, 60 mg qd or warfarin dose adjusted to international normalised ratio of 2–3 for three months. The primary endpoint was the incidence of centrally adjudicated all bleeding events (major, clinically relevant non-major and minor). Secondary endpoints included thromboembolic events, biomarkers of thrombus formation and all adverse events (AEs). The incidence of all bleeding events (95% CI) was 20.3% (12.9, 30.4) for edoxaban 30 mg, 23.8% (15.8, 34.1) for edoxaban 60 mg, and 29.3% (20.2, 40.4) for warfarin. A subgroup analysis suggested low body weight (≤60 kg) may affect the incidence of bleeding events with edoxaban. The incidence of study drug-related AEs was 22% for edoxaban 30 mg, 29% for edoxaban 60 mg and 33% for warfarin. No thromboembolic events occurred in any treatment group. In conclusion, this phase II study found a trend for a reduction in the incidence of all bleeding events in Asian AF patients with edoxaban 30 mg and 60 mg compared with warfarin. Adverse events were similar between the edoxaban 60-mg and warfarin groups and were lower with the edoxaban 30-mg group.ClinicalTrials.gov number: NCT00806624
Keywords: Edoxaban; non-valvular atrial fibrillation; factor Xa inhibitor; anticoagulant; warfarin